The Strategy of Turn-Taking in Pygmalion by George Bernard Shaw - Najlaa Hayyawi Abbar (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article examines the turn-taking system and adjacency pairs in George Bernard Shaw's play